K-pop : popular music, cultural amnesia, and economic innovation in South Korea - Lie, John (University of California Press, 2015)
"K-Pop: Popular Music, Cultural Amnesia, and Economic Innovation in South Korea seeks at once to describe and explain the emergence of export-oriented South Korean popular music and to make sense of larger South Korean economic and cultural transformations. John Lie provides not only a history of South Korean popular music--the premodern background, Japanese colonial influence, post-Liberation American impact, and recent globalization--but also a description of K-pop as a system of economic innovation and cultural production. In doing so, K-Pop delves into the broader background of South Korea that gave rise to K-pop in this wonderfully informed history and analysis of a pop culture phenomenon sweeping the globe"--Provided by publisher